The Influence of Metabolism on Drug Response in Cancer - Zaal, Esther A.; Berkers, Celia R. (Frontiers in Oncology, 2018)
Resistance to therapeutic agents, either intrinsic or acquired, is currently a major problem in the treatment of cancers and occurs in virtually every type of anti-cancer therapy. Therefore, understanding how resistance can be prevented, targeted and predicted becomes increasingly important to improve cancer therapy. In the last decade, it has become apparent that alterations in cellular metabolism are a hallmark of cancer cells and that a rewired metabolism is essential for rapid tumor growth and proliferation. Recently, metabolic alterations have been shown to play a role in the sensitivity of cancer cells to widely-used first-line chemotherapeutics. This suggests that metabolic pathways are important mediators of resistance towards anticancer agents. In this review, we highlight the metabolic alterations associated with resistance towards different anticancer agents and discuss how metabolism may be exploited to overcome drug resistance to classical chemotherapy.